Locationals in Oromo - Mi’eesa Yaachis (LibraryPress@UF, 2012)
This is a study of the locational structures of Oromo. A range of syntactic constructions types is considered within a single synchronic grammaticalization schema. Speaker choices of particular structures within discourse are also identified and explored. The primary data are drawn from the Guji dialect, with reference to data from other dialects that are attested in the literature. Most of the morphological marking that is found across these locationals is consistent in all Oromo speech communities, and, although there is some variation in some particular lexemes across the dialects, the inventories of locational lexemes are interlocking and nearly entirely overlapping.